2011
DOI: 10.1002/anie.201006496
|View full text |Cite
|
Sign up to set email alerts
|

Modular Design in Natural and Biomimetic Soft Materials

Abstract: Under eons of evolutionary and environmental pressure, biological systems have developed strong and lightweight peptide-based polymeric materials by using the 20 naturally occurring amino acids as principal monomeric units. These materials outperform their man-made counterparts in the following ways: 1) multifunctionality/tunability, 2) adaptability/stimuli-responsiveness, 3) synthesis and processing under ambient and aqueous conditions, and 4) recyclability and biodegradability. The universal design strategy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
165
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 204 publications
(168 citation statements)
references
References 454 publications
(441 reference statements)
1
165
0
1
Order By: Relevance
“…One of the internal block repeats, the 36-amino acid segment, could be divided into the following submotifs: 1) five tandem copies of the pentameric sequence X 1 PGGX 2 ; 2) one hexameric sequence RPGGKG; and 3) one pentameric sequence QPGYY. These 36-amino acid block repeats were iterated 11 times, comprising over 55 copies of the X 1 PGGX 2 subrepeats; these pentameric sequences resemble VPGXG repeats found within elastin (35). Structurally, VPGXG iterations have been proposed to adopt a longrange ␤-spiral conformation with spring-like structures (36,37).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One of the internal block repeats, the 36-amino acid segment, could be divided into the following submotifs: 1) five tandem copies of the pentameric sequence X 1 PGGX 2 ; 2) one hexameric sequence RPGGKG; and 3) one pentameric sequence QPGYY. These 36-amino acid block repeats were iterated 11 times, comprising over 55 copies of the X 1 PGGX 2 subrepeats; these pentameric sequences resemble VPGXG repeats found within elastin (35). Structurally, VPGXG iterations have been proposed to adopt a longrange ␤-spiral conformation with spring-like structures (36,37).…”
Section: Discussionmentioning
confidence: 99%
“…Structurally, VPGXG iterations have been proposed to adopt a longrange ␤-spiral conformation with spring-like structures (36,37). Whether iterations of X 1 PGGX 2 sequences fold into a similar secondary structure is unclear, but the PG residues and their presence in the pentameric modules strikingly resemble the VPGXG and GPGQQ modules of elastin and the flagelliform fibroin in spiral capture silk, respectively (13,35). Despite these similarities, there are some differences between the VPGXG and X 1 PGGX 2 modules.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore some proteins, such as actin 1 , collagen 2 and amyloid 3 , form fibrils held together by intermolecular interactions. As these sophisticated structures can be constructed without special equipment, fibrils made of either natural or artificial proteins have been studied for use in various functional materials [4][5][6] . For example, fibrils have been used as scaffolds for metals 7,8 and functional proteins 9,10 and as networks for tissue engineering applications 11 .…”
mentioning
confidence: 99%
“…The reader is referred to this article for a detailed explanation about these natural peptide-based materials and how mimicking nature's approach leads to a new generation of advanced materials bearing useful properties that exceed those available by current methods. 48 Hubbell et al reported on the development of a coating of surface-active copolymers that are RGD grafted to induce specific cell attachment and spreading and contained poly(ethylene glycol) (PEG) in order to prevent nonspecific protein adsorption. A poly-(L-lysine) (PLL) backbone from which PEG was grafted with short and long chains was synthesized.…”
Section: Supramolecular Biomaterials Inspired By Peptides and Peptidementioning
confidence: 99%